Thermophiles; or, the Modern Prometheus: The Importance of Extreme Microorganisms for Understanding and Applying Extracellular Electron Transfer - Lusk, Bradley G. (Frontiers in Microbiology, 2019)
Approximately four billion years ago, the first microorganisms to thrive on earth were anaerobic chemoautotrophic thermophiles, a specific group of extremophiles that survive and operate at temperatures ∼50 – 125°C and do not use molecular oxygen (O2) for respiration. Instead, these microorganisms performed respiration via dissimilatory metal reduction by transferring their electrons extracellularly to insoluble electron acceptors. Genetic evidence suggests that Gram-positive thermophilic bacteria capable of extracellular electron transfer (EET) are positioned close to the root of the Bacteria kingdom on the tree of life. On the contrary, EET in Gram-negative mesophilic bacteria is a relatively new phenomenon that is evolutionarily distinct from Gram-positive bacteria. This suggests that EET evolved separately in Gram-positive thermophiles and Gram-negative mesophiles, and that EET in these bacterial types is a result of a convergent evolutionary process leading to homoplasy. Thus, the study of dissimilatory metal reducing thermophiles provides a glimpse into some of Earth’s earliest forms of respiration. This will provide new insights for understanding biogeochemistry and the development of early Earth in addition to providing unique avenues for exploration and discovery in astrobiology. Lastly, the physiological composition of Gram-positive thermophiles, coupled with the kinetic and thermodynamic consequences of surviving at elevated temperatures, makes them ideal candidates for developing new mathematical models and designing innovative next-generation biotechnologies. KEY CONCEPTS Anaerobe: organism that does not require oxygen for growth. Chemoautotroph: organism that obtains energy by oxidizing inorganic electron donors. Convergent Evolution: process in which organisms which are not closely related independently evolve similar traits due to adapting to similar ecological niches and/or environments. Dissimilatory Metal Reduction: reduction of a metal or metalloid that uses electrons from oxidized organic or inorganic electron donors. Exoelectrogen: microorganism that performs dissimilatory metal reduction via extracellular electron transfer. Extremophiles: organisms that thrive in physical or geochemical conditions that are considered detrimental to most life on Earth. Homoplasy: a character shared by a set of species that is not shared by a common ancestor Non-synonymous Substitutions (Ka): a substitution of a nucleotide that changes a codon sequence resulting in a change in the amino acid sequence of a protein. Synonymous Substitutions (Ks): a substitution of a nucleotide that may change a codon sequence, but results in no change in the amino acid sequence of a protein. Thermophiles: a specific group of extremophiles that survive and operate at temperatures ∼50–125°C.